Apple Russet Ring and Apple Green Crinkle Diseases: Fulfillment of Koch’s Postulates by Virome Analysis, Amplification of Full-Length cDNA of Viral Genomes, in vitro Transcription of Infectious Viral RNAs, and Reproduction of Symptoms on Fruits of Apple Trees Inoculated With Viral RNAs - Li, Chunjiang; Yaegashi, Hajime; Kishigami, Ryusuke; Kawakubo, Ayaka; Yamagishi, Noriko; Ito, Tsutae; Yoshikawa, Nobuyuki (Frontiers in Microbiology, 2020)
Apple russet ring and apple green crinkle are graft-transmitted diseases first reported more than 60 years ago, but at present, no association between a specific virus (variant) and the disease has been clearly demonstrated. In this study, we conducted the following series of experiments to identify the causal viruses (variants) of these apple diseases; 1) comprehensive analysis by next-generation sequencing of all viruses in each apple tree affected with russet ring or green crinkle disease, 2) amplification of full-length genomic cDNA of viruses using primers containing the T3 promoter and the in vitro transcription of infectious viral RNAs, 3) inoculation of viral RNA transcripts to both herbaceous and apple plants, 4) analysis of sequence variants of viruses present in infected plants, 5) back-inoculation of sequence variants of candidate viruses to apple seedlings combined with the virus-induced flowering technology using the apple latent spherical virus vector to reproduce the symptom on the fruit as soon as possible, and 6) reproduction of symptoms on the fruits of apple trees inoculated with sequence variants and the re-isolation of each virus variant from apples showing fruit symptoms. The results showed that one of the sequence variants of the apple chlorotic leaf spot virus causes a characteristic ring-shaped rust on the fruits of infected apple trees and that a sequence variant of the apple stem pitting virus probably causes green crinkle symptoms on an infected apple fruit. Thus, we were able to fulfill Koch’s postulates to prove the viral etiology of both the apple russet ring and green crinkle diseases. We also propose an experimental system that can prove whether a virus found in diseased tissues is the pathogen responsible for the diseases when the etiology is undetermined.